Evaluation of Medical Sciences Students’ Perception, Barriers, and Attitude toward Scientific Research: A Cross-sectional Study in Makkah Region, Saudi Arabia - Ahmed, Nehad J (Asian Journal of Pharmaceutics (AJP), 2021)
Aim: Medical research skills at the undergraduate level is increasingly discussed as having a potential role in developing certain skills in students including decision making, problem-solving, and critical thinking. Therefore, this study aimed to evaluate the perception, barriers, and attitude of medical sciences students toward scientific research in Makkah region of Saudi Arabia. Methods: The data collected between August and September 2019 using an electronic questionnaire that was distributed to medical sciences students at Makkah region including (4th, 5th, 6th years, and interns). Results: Total number of participants who answered the questionnaire was 411 health-care students. Most of the students were females (70.6%), only 29.4% of them were male students. Most of them (72.8%) agreed that scientific research is essential for undergraduate students and about 73.2% of them said that they will participate in any available research opportunity. About 70.3% of the respondents reported that they do not know whom to contact if they want to conduct research and about 61.6% of the respondents reported there were few opportunities to do research in their college. Conclusion: Although students have good attitude and good perception toward research, there are some barriers that should be overcome to encourage student participation in research activities in Makkah region’s universities of Saudi Arabia.